Borderline personality disorder, trauma, and the hypothalamus–pituitary–adrenal axis - Thomas N (Dove Medical Press, 2019)
Natalie Thomas, Caroline Gurvich, Jayashri Kulkarni Central Clinical School , Monash Alfred Psychiatry Research Centre, Monash University, Melbourne, Victoria, AustraliaCorrespondence: Natalie ThomasMonash Alfred Psychiatry Research Centre, Monash University, Level 4, 607 Street Kilda Road, Melbourne, Victoria 3004, AustraliaTel +61 39 076 5033Email natalie.thomas@monash.eduAbstract: Borderline personality disorder (BPD) is a complex psychiatric illness for which treatment poses a significant challenge due to limited effective pharmacologic treatments, and under-resourced psychological interventions. BPD is one of the most stigmatized conditions in psychiatry today, but can be understood as a modifiable, neurodevelopmental disorder that arises from maladaptive responses to trauma and stress. Stress susceptibility and reactivity in BPD is thought to mediate both the development and maintenance of BPD symptomatology, with trauma exposure considered an early life risk factor of development, and acute stress moderating symptom trajectory. An altered stress response has been characterized in BPD at the structural, neural, and neurobiological level, and is believed to underlie the maladaptive behavioral and cognitive symptomatology presented in BPD. The endocrine hypothalamus–pituitary–adrenal (HPA) axis represents a key stress response system, and growing evidence suggests it is dysfunctional in the BPD patient population. This theoretical review examines BPD in the context of a neurodevelopmental stress-related disorder, providing an overview of measurements of stress with a focus on HPA-axis measurement. Potential confounding factors associated with measurement of the HPA system are discussed, including sex and sex hormones, genetic factors, and the influence of sample collection methods. HPA-axis dysfunction in BPD largely mirrors findings demonstrated in post-traumatic stress disorder and may represent a valuable neuroendocrine target for diagnostic or treatment response biomarkers, or for which novel treatments can be investigated.Keywords: borderline personality disorder, hypothalamus–pituitary–adrenal axis, trauma, stress